Dear Me Beauty for Beauty Inclusivity in Empowering Women to Conquer their Insecurity: Positive Multimodal Discourse Analysis - Zahra Naila La Zinu; Muhammad Hafiz Kurniawan (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2025)
Beauty inclusivity and diversity have been echoed to give a chance to other races and other types of beauty are represented. This study analyzes Dear Me Beauty advertisements in Instagram reels using Appraisal Theory (Martin &White, 2005) to analyze the verbal elements and Visual Grammar Theory (Kress & Leeuwen, 2021) to analyze the visual representation. This research aims to explore how Dear Me Beauty communicates the discourse of inclusivity through visual representation of models with various skin colors and inclusive language in caption and product descriptions. The research employed a descriptive qualitative approach to examine visual and verbal elements present in Dear Me Beauty advertisements within a multimodal framework. The findings reveal that Positive Appreciation (65.28%) and Affect (21.96%) dominate the verbal discourse, highlighting the brand’s focus on empowerment, diversity, and self-acceptance. Graduation patterns indicate frequent upscaling and intensification, reinforcing optimism and inclusivity. Visual representation shows the dominance of unidirectional and non-transactional actions, balanced gaze, and equal social distance construct authenticity and approachability. This research contributes to the field of multimodal discourse analysis and offer practical implications for advertisers and scholars interested in understanding the discourse of inclusivity through advertisements.